The Influence of Brand Ambassadors, Viral Marketing, and Online Customer Reviews on Purchase Decisions on Online Shopping Applications in Sidoarjo Regency: Pengaruh Duta Merek, Pemasaran Viral, dan Ulasan Pelanggan Online Terhadap Keputusan Pembelian Pada Aplikasi Belanja Online di Kabupaten Sidoarjo - Akfinniha, Rizki; Sari, Dewi Komala (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the influence of Brand Ambassador, Viral Marketing, and Online Custommer Review on Purchasing Decisions. This research uses a quantitative approach. Sampling in the study using accidental sampling techniques, with the number of respondents as many as 100 respondents from marketplace shopee.id consumers. Data collection techniques using questionnaires distributed through questionaire. Data analysis techniques in this study use multiple linear regression analysis. Data processing in this study using the SPSS 22 (Statistical Program For the Social Sciences) software program. The result of this study, show result that can prove that Brand Ambassador has an affects on Purchasing Decisions of marketplace shopee.id, Viral Marketing, has an affects on Purchasing Decisions of marketplace shopee.id, and Online Custommer Review an affects of Purchasing Decisions for marketplace shopee.id user in Sidoarjo.